2015
DOI: 10.1371/journal.pone.0133667
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Survey and Analysis of Microsatellite Sequences in Bovid Species

Abstract: Microsatellites or simple sequence repeats (SSRs) have become the most popular source of genetic markers, which are ubiquitously distributed in many eukaryotic and prokaryotic genomes. This is the first study examining and comparing SSRs in completely sequenced genomes of the Bovidae. We analyzed and compared the number of SSRs, relative abundance, relative density, guanine-cytosine (GC) content and proportion of SSRs in six taxonomically different bovid species: Bos taurus, Bubalus bubalis, Bos mutus, Ovis ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 52 publications
10
43
2
Order By: Relevance
“…A, R 2 = 0.8992, P < 0.01). This phenomenon was the same as that for 30 marine species reported (Jiang et al ., ) and six bovid species (Qi et al ., ), in which the genome sizes were also correlated with the SSR numbers. SSRs are supposed to contribute to larger genome sizes since the accumulation of genes is not responsible for large differences in genome size (Jiang et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A, R 2 = 0.8992, P < 0.01). This phenomenon was the same as that for 30 marine species reported (Jiang et al ., ) and six bovid species (Qi et al ., ), in which the genome sizes were also correlated with the SSR numbers. SSRs are supposed to contribute to larger genome sizes since the accumulation of genes is not responsible for large differences in genome size (Jiang et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Whole‐genome SSR detection has been reported in plants such as Oryza minuta and Or. punctata (Wang et al ., ), Sesamum indicum (Wei et al ., ), and Ziziphus jujuba (Xiao et al ., ) and in 30 marine animals (Jiang et al ., ), six species of birds (Huang et al ., ), six species of bovids (Qi et al ., ), Apis cerana (Liu et al ., ) and Tribolium castaneum (Demuth et al ., ). The SSRs in coding sequences (CDs) of 25 insect species have been identified and comparatively analyzed (Behura & Severson, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the bovid genomes, mononucleotides SSRs were also the most abundant repeat type, accounting for 43.01% – 45.33% of all SSRs, followed by the pattern: di- > tri- > Penta- > tetra- > hexanucleotides SSRs. It has been reported that the abundance of mononucleotide SSRs are more than other nucleotide SSRs in eukaryotic genomes [26,27]. Also, mononucleotide SSRs are the most abundance in all human chromosomes [28].…”
Section: Discussionmentioning
confidence: 99%
“…The intergenic regions referred to the interval sequences between gene and gene that were not included the introns, CDSs, UTRs, and other sequences. SSRs can be grouped into six categories [26,61,62], which were identified and scanned for SSRs of 1-6 bp using the software MSDB (Microsatellite Search and Building Database) downloaded at https://code.google.com/p/msdb/ [63]. To compare our results, we performed a similar analysis of these primate genomes using the same bioinformatics tool and search parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation